METHOD OF DETERMINATION OF THE FIRST PLAYER OPTIMAL STRATEGIES IN A SUBCLASS OF THE NONSTRICTLY CONVEX ANTAGONISTIC GAMES - Romanuk, V. V. (Radio Electronics, Computer Science, Control, 2010)
By the example of two nonstrictly convex antagonistic games, where the second player has the single optimal pure strategy, it has been asserted, that there exists a subclass of nonstrictly convex antagonistic games, in which by the known method there cannot be determined the optimal probabilities of selecting the essential pure strategies of the first player. It has been demonstrated that to determine them, it is sufficient to employ the saddle point concept in the known optimality principle by applying the corresponding right-side inequality.